Physico-mathematical modeling methods for the pressure distribution determination in the gas-dynamic bearing gap of the ball gyroscope; MATEC Web of Conferences; Vol. 102 : Space Engineering - Ignatovskaya A. A. Anastasiya Albertovna (2017, 2017)
Title screen